ANALISIS PEMIDANAAN TERHADAP ANAK SEBAGAI PENGEDAR NARKOTIKA DALAM PERSPEKTIF PSIKOLOGI KRIMINAL - Yulia Utami; Muhamad Hasan Sebyar (INTELIGENSIA MEDIA, 2023)
This study aims to determine the efforts in preventing children from becoming drug dealers and to understand the role of criminal psychology as a benchmark in imposing penalties on children. The research method used in this study is empirical, which focuses on empirical facts derived from human behavior, including verbal behavior obtained from interviews and actual behavior observed through direct observation. The results of this research show that the sentencing of children involved in drug trafficking. Judges make decisions based on sentencing theory, particularly the combined theory, where judges impose prison sentences as a deterrent and provide vocational training as a rehabilitative aspect. However, economic reasons consistently serve as a shield in mitigating sentences for children. In criminological theory, criminal actions do not exist in isolation, which is why criminal psychology plays a crucial role in balancing the imposition of penalties on children